Corporate Governance dan Kinerja Keuangan Perusahaan Pertambangan Indonesia - Putri Exsanti; Yuliani Yuliani; Shelfi Malinda (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2023)
This study aims to analyze the effect of corporate governance on financial performance. Financial performance is measured based on market value using the Tobin's Q model. Meanwhile, corporate governance is seen from the principle of independence by using managerial ownership, institutional ownership, and the size of the independent board of commissioners as proxies. Based on the purposive sampling method, 35 mining sector companies were selected which were listed on the Indonesia Stock Exchange with the 2016-2020 observation period so that 175 observation units were obtained. The data analysis technique uses multiple linear regression. The results showed that managerial ownership and institutional ownership had no effect on financial performance, while the size of the independent board of commissioners had a significant negative effect on financial performance. This shows that the number of shares owned by the company's management as well as private and government ownership does not affect the company's financial performance. Meanwhile, the greater the number of independent commissioners, the lower the company's financial performance based on market value. This could have been caused by a negative investor assessment that reduced demand for company shares, which in turn had an impact on a decrease in the company's market value. So, the company is advised to increase the number of independent commissioners. For further research it is suggested to use audit quality as another proxy and analyze the principles of Good Corporate Governance in a comprehensive manner.